OP11 Are simple non-invasive scoring systems for fibrosis reliable in patients with NAFLD and normal ALT levels?. (6th September 2011) - McPherson, S; Anstee, Q; Henderson, E; Burt, A; Day, C
Abstract : Introduction: With a quarter of the UK population estimated to have some degree of NAFLD, there is a need for a robust and economical population based screen to identify individuals with advanced fibrosis. It is recognised that many patients with NAFLD have normal-range ALT levels. Non-invasive scoring systems may exclude advanced disease without the need for liver biopsy, however reliability of these tests in this population has not been determined. Aim: To assess performance of several simple non-invasive tests for fibrosis in patients with biopsy-proven NAFLD and normal ALT levels. Method: Patients who were reviewed in the Freeman Hospital fatty liver clinic between 1999 and 2009 were included. Liver biopsies were assessed using the Kleiner score. The AST/ALT ratio, BARD, FIB-4 and NAFLD fibrosis scores were calculated from blood tests taken within 6 months of liver biopsy. Results: 305 patients were included (70 with normal ALT [ALT <30 IU/l for females and ALT <45 IU/l for males] and 235 with raised ALT). 24% of subjects with normal ALT and 17% with raised ALT had advanced fibrosis (Kleiner stage 3–4). Patients with normal ALT were significantly younger (p=0.004) and had lower BMI (p=0.03) than those with raised ALT. The area under ROC curve (AUROC), sensitivity, specificity, positive and negative predictive values for a diagnosis of advanced fibrosis using each score is shown in Abstract OP11 table 1 . In addition, the proportion of patients with a score below the cut-off who would avoid liver biopsy is displayed. The specificity of the AST/ALT ratio, BARD and NAFLD fibrosis scores for advanced fibrosis was low in patients with normal ALT, which would result in a high proportion of patients with mild disease having a liver biopsy. FIB-4 score performed best overall. Conclusion: The FIB-4 score performed well in patients with normal or raised ALT, reliably excluding advanced fibrosis and reducing the need for liver biopsy. Therefore, the FIB-4 score may be an appropriate tool for use in primary care to triage patients with NAFLD who need referral for further assessment. Further validation in a general practice cohort is underway.